Increased activation of lymphocytes infiltrating primary colorectal cancers following immunisation with the anti-idiotypic monoclonal antibody 105AD7. Issue 4 (1st October 1999) - Maxwell-Armstrong, C A; Durrant, L G; Robins, R A; Galvin, A M; Scholefield, J H; Hardcastle, J D
Abstract : BACKGROUND: The anti-idiotypic monoclonal antibody 105AD7 mimics the tumour associated antigen 791Tgp72, expressed on 70–80% of colorectal cancers. Phase I studies have shown that the vaccine is non-toxic, and a number of patients have been immunised prior to resection of their primary tumours. AIMS: To assess lymphocyte activation at the tumour site by measuring expression of the α subunit of the interleukin 2 receptor (CD25). METHODS: Nineteen patients with primary colorectal cancer were immunised with varying doses of 105AD7 prior to resection of their primary tumours. Samples of normal bowel and tumour edge/centre from 16 patients were available for immunohistochemical staining with a monoclonal antibody against CD25. Samples from a matched control group were also stained. Fresh tumours from 14 immunised patients and 31 unimmunised control patients were disaggregated, and the lymphocytes obtained labelled for CD25. Samples were analysed blindly by flow cytometry. RESULTS: Median infiltration of lymphocytes expressing CD25, measured immunohistochemically, was higher in trial patients, as was the ratio of tumour to normal bowel infiltration. Flow cytometric analysis of fresh tumour from immunised patients showed a significantly higher percentage of lymphocytes expressing CD25 tumour infiltrating lymphocytes than their matched and unmatched controls. DISCUSSION: The α subunit of the interleukin 2 receptor is increased on tumour infiltrating lymphocytes, in patients immunised with the colorectal cancer vaccine 105AD7. This suggests a population of activated lymphocytes capable of targeting 791Tgp72 expressing tumour cells, such as circulating micrometastases. 105AD7 may have a role as adjuvant therapy in early stage disease.